Parental Education and Children's Schooling Outcomes: Evidence from Recomposed Families in Rwanda - de Walque, Damien (2012)
In this article, I investigate how educational outcomes of orphans are affected by the education of the family members in their new family. The study uses household survey data from Rwanda that contain a large proportion of children living in households without their biological parents. The data also allow controlling for the educational attainment of the absent biological parents and the type of relationship that links the children to their adoptive families. The results of the analysis suggest that the education of the adoptive parents has a positive impact on the children's schooling. Interestingly, mothers' education matters more for girls, while fathers' education is more important for boys. The results also indicate that placing orphans with their relatives has a positive impact on their schooling. This finding has obvious policy implications for African countries with a large proportion of orphans due to the HIV/AIDS epidemic or to conflicts.